Medieval knights - Abdo, Kenny, 1986- (Abdo, Kenny, 1986- Ancient warriors., 2021)
Presents the history, warfare and tactics, and weapons of medieval knights, and highlights the modern-day adaptations of medieval knights. Includes color photographs, a glossary, and additional resources.